A Review of Studies Leveraging Multimodal TMS-fMRI Applications in the Pathophysiology and Treatment of Schizophrenia - Baliga, Sachin Pradeep; Mehta, Urvakhsh Meherwan (Frontiers in Human Neuroscience, 2021)
The current review provides an overview of the existing literature on multimodal transcranial magnetic stimulation, and functional magnetic resonance imaging (TMS/fMRI) studies in individuals with schizophrenia and discusses potential future avenues related to the same. Multimodal studies investigating pathophysiology have explored the role of abnormal thalamic reactivity and have provided further evidence supporting the hypothesis of schizophrenia as a disorder of aberrant connectivity and cortical plasticity. Among studies examining treatment, low-frequency rTMS for the management of persistent auditory verbal hallucinations (AVH) was the most studied. While multimodal TMS/ fMRI studies have provided evidence of involvement of local speech-related and distal networks on stimulation of the left temporoparietal cortex, current evidence does not suggest the superiority of fMRI based neuronavigation over conventional methods or of active rTMS over sham for treatment of AVH. Apart from these, preliminary findings suggest a role of rTMS in treating deficits in neurocognition, social cognition, and self-agency. However, most of these studies have only examined medication-resistant symptoms and have methodological concerns arising from small sample sizes and short treatment protocols. That being said, combining TMS with fMRI appears to be a promising approach towards elucidating the pathophysiology of schizophrenia and could also open up a possibility towards developing personalized treatment for its persistent and debilitating symptoms.